(untitled) (Research, Society and Development, 2025)
Alzheimer’s disease (AD) is a progressive and irreversible neurodegenerative condition that affects cognitive functions, being associated with reduced acetylcholine levels. Although there is no cure, acetylcholinesterase (AChE) inhibitors are used to slow symptom progression. Phytochemical compounds with anticholinesterase activity have been studied as promising therapeutic alternatives, particularly through in vitro and in silico techniques. This systematic review aimed to identify phytochemicals with AChE inhibitory potential in studies published between 2020 and 2025, using the PubMed and Science Direct databases. Six articles met the inclusion and exclusion criteria. The compounds investigated belong to the classes of alkaloids, flavonoids, isoflavonoids, and tannins. Among the alkaloids, lahorine, bulbocapnine, and a benzodioxole derivative showed strong affinities with AChE, with binding energies ranging from −11.26 to −12.65 kcal·mol⁻¹. Huperzine B stood out for its positive results in biological assays. Flavonoids such as apigenin, amentoflavone, and isoquercitrin demonstrated strong interactions, especially through hydrogen bonding with the enzyme’s catalytic residues. Aglycone flavonoids proved more effective than their glycosylated forms. Flavonoids such as apigenin, amentoflavone, and isoquercitrin demonstrated strong interactions, especially via hydrogen bonding with the enzyme’s catalytic residues, with aglycone flavonoids proving more effective than their glycosylated forms. Isoflavonoids such as genistein and vitexin showed binding energies up to −12.5 kcal·mol⁻¹. Although ellagic acid was less potent in vitro, it exhibited multiple structural interactions. The findings highlight polycyclic alkaloids and aglycone flavonoids as promising classes for the development of new AChE inhibitors. Integration of silico, in vitro, and pharmacokinetic/toxicological studies is essential for therapeutic validation and advances in AD treatment.